Internet usage and the effects towards students of private institutions Emotional Well-Being (EWB) / Che Nur Amalina S. Che Zainal … [et al.] - Che Zainal, Che Nur Amalina S.; Amat @ Adnin, Norfarahin; Raja Abdullah, Raja Rosemawati; Abdul Rahman, Mohd Asyraf; Bahari, Shazni (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The direction of the correlation between Internet use and emotional well-being is debatable. Young adults face different stressors in their transition to college. Negative emotions such as stress can emerge from the demands they face. This paper analyses the effects of internet usage on the Emotional Well-Being (EWB) among students in private institutions in the Klang Valley. Nowadays, internet usage has become an important tool for social interaction, information, and entertainment. This worldwide situation resulted in the increment on internet users throughout the year especially among youngsters including in Malaysia. Indeed, Malaysia stands out as a developing country with the fourth-highest proportion of digital natives in the world. The researcher conducted a behavioral study, characterized as explanatory-descriptive, by applying a questionnaire survey adopted from Emotional Well Being Scale (EWBS) to collect data to a group of 150 private university students from both Kolej Universiti Poly-Tech MARA (KUPTM) and International University of Malaya-Wales (IUMW). Our findings suggest that the internet usage resulted in both positive and negative emotional well-being. Type of Internet use, indicator of well-being, quality of Internet use measure, and participants age and gender were among the indicators that may affect the overall results of the study.